Evaluating drought tolerance of castor ecotypes in the center of Iran. Issue 4 (April 2019) - Nikneshan, Pejman; Tadayyon, Ali; Javanmard, Milad
Abstract: In order to study the reaction of six castor ecotypes to drought stress, a split plot experiment was carried out in randomized complete blocks. Eight indices including stress sensitivity index (SSI), tolerance index (TOL), mean productivity (MP), geometric mean productivity (GMP), harmonic mean (HARM), stress tolerance index (STI), sensitivity drought index (SDI) index and yield index (YI) were calculated for ecotypes by using seed yield in normal condition and under stress. After that, correlations between indices were calculated and dendrogram and biplot results were drawn. Normal yield and stress yield had positive significant correlations with MP, GMP, STI, and HARM indices in mild, moderate and severe stresses. Biplot analysis showed that Isfahan and Naein ecotypes had desirable yield under mild and average stress and Naein had desirable yield under severe stress and also normal condition.